Analysis of Fiscal Reconciliation and Application of PMK Number 169/PMK.010/2015 to Commercial Financial Reports in Determining the Income Tax Payable for 2018 (Case Study at PT LBAS) - I W S A Gunawan; W H Utthavi; L M Wahyuni (Journal of Applied Sciences in Accounting, Finance, and Tax, 2020)
Tax is one of the biggest source of incomes to increase development and welfare of people's lives but for companies, taxes are considered as a burden in obtaining maximum profit. For this reason, taxation arrangements are needed in accordance with existing regulatory requirements to minimize tax payments. PT LBAS is a company engaged in hospitality services aiming to obtain maximum profit. One way to reach that goal is by making fiscal correction in accordance with applicable tax regulations. The type of data in this study is quantitative and qualitative, and data source is secondary obtained through documentation. The results of this qualitative-descriptive research are PT LBAS financial statements that are not in accordance with tax regulations relating to net income before taxes increased to Rp4,467,665,861.00, the amount of tax underpaid amounting to Rp524,264,758.00. Therefore, when making corrections the company is required to pay off the calculation of the debt equity ratio and nominative list in order to minimize the request for inspection by the tax authorities.